2020
DOI: 10.1155/2020/3170803
|View full text |Cite
|
Sign up to set email alerts
|

The Combinatorial Effect of Cisplatin and Moxibustion on Tumor Growth Inhibition with Special Reference to Modulation of the Immune Microenvironment in Lewis Lung Cancer Mice

Abstract: Objective. As a first-line treatment for non-small cell lung cancer (NSCLC), the efficacy of chemotherapy is still unsatisfactory. Moxibustion has been shown to improve the side effects of radiotherapy and chemotherapy and regulate immune function. This study aimed to explore the antitumor effects and potential mechanisms of combinatorial cisplatin and moxibustion treatment for NSCLC by targeting the tumor microenvironment. Methods. Lewis lung cancer (LLC)-bearing mice were induced and treated with cisplatin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 40 publications
1
18
1
Order By: Relevance
“…The results confirmed that compared with the treatment of tropisetron hydrochloride alone, the combined acupuncture treatment can improve the life quality of the patients to a greater extent, which is beneficial to the improvement of the patient's physical function status, and the patient's self-confidence in treatment is significantly improved. The patient was treated with chemotherapy, and the side effects and white blood cell count decreased significantly [ 20 22 ]. The results of combined acupuncture and drug treatment showed that the white blood cell counts of the three groups were significantly reduced after treatment, but the difference between the groups was not statistically significant ( P > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The results confirmed that compared with the treatment of tropisetron hydrochloride alone, the combined acupuncture treatment can improve the life quality of the patients to a greater extent, which is beneficial to the improvement of the patient's physical function status, and the patient's self-confidence in treatment is significantly improved. The patient was treated with chemotherapy, and the side effects and white blood cell count decreased significantly [ 20 22 ]. The results of combined acupuncture and drug treatment showed that the white blood cell counts of the three groups were significantly reduced after treatment, but the difference between the groups was not statistically significant ( P > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Moxibustion is an effective supportive cancer care in inhibiting tumor growth [25,26] and alleviating side effects of chemotherapy and radiotherapy [27]. Such as, moxibustion can inhibit nausea and vomiting after chemotherapy…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also showed that cisplatin inhibited all leukocyte subpopulations and was more detrimental to T lymphocytes than to B lymphocytes in xenograft mice. This indicates the potential of cisplatin to induce immunosuppression and limit antitumor immune responses ( 61 ). Based on the fact that acupoint stimulation can improve myelosuppression and immunosuppression caused by cisplatin, and BM hematopoiesis is an important source of immune cell subgroups in the tumor immune microenvironment (TIME), we speculate that acupoint stimulation may contribute to the inhibition of tumor growth and the improvement of the TIME via recovery of BM hematopoiesis.…”
Section: Efficacy and Mechanisms Of Acupoint Stimulation In The Allev...mentioning
confidence: 99%
“…Basic research on the tumor-inhibiting effects and mechanisms of acupoint stimulation has also been conducted. In this review, we retrieved seven basic studies, which showed that acupoint stimulation with chemotherapy could delay tumor growth and metastasis to some extent in mice with breast cancer ( 60 , 62 ), osteosarcoma ( 63 , 64 ), colon cancer ( 65 ), and non-small cell lung cancer ( 61 ) models and could prolong survival in mice (shown in Table 4 ).…”
Section: The Efficacy and Mechanism Of Acupoint Stimulation On Tumor ...mentioning
confidence: 99%
See 1 more Smart Citation